Dampak Pandemi Covid-19 Terhadap Aktivitas Pengauditan - Manihuruk, Widiya Anastasya; Butar Butar, Sansaloni (JURNAL AKUNTANSI, 2023)
This study investigates the impact of the COVID-19 pandemic on the auditing activities of Indonesian public companies. During a pandemic auditing activities are predicted to affect the auditor's opinion regarding going concern, audit delay, audit opinion, and the decision to use Big-4 versus non-Big-4 auditors. A sample was selected from tourism and manufacturing companies from 2018-2021 due to the severe impact of COVID-19 on these two sectors. The results of the quantitative analysis show that: 1) Auditors issued more going-concern opinions during the Covid-19 pandemic. 2) Auditors spent more time completing auditing tasks during the Covid-19 pandemic. 3) The number of qualified opinions was relatively similar in the pre-pandemic period and during the Covid-19 pandemic. 4) Clients using Big-4 KAPs decreased during the pandemic. In addition, the content analysis shows: 1) More going concern audit opinions should have been issued during the pandemic than currently available. Some auditors seem to deliberately not mention explicitly the impact of Covid 19 on the continuity of the company. 2) Only a small number of companies disclose the impact of Covid 19 on the company's financial performance.